Fair Value Accounting Measurement Reliability and Market Volatility Effects (gjstudies, 2025)
This research investigates the complex relationship between the reliability of fairvalue accounting measurements and their subsequent effects on market volatility, atopic that remains underexplored in the accounting literature. While prior studieshave examined the general impact of fair value accounting on financial reporting, thispaper uniquely focuses on the measurement reliability spectrum—from Level 1 (observable market prices) to Level 3 (unobservable model-based inputs)—and how differentreliability levels asymmetrically influence market behavior during periods of economicstress. We develop a novel methodological framework that integrates accounting measurement theory with behavioral finance principles, creating a hybrid approach thatcaptures both the technical measurement challenges and the psychological market responses. Our research employs a multi-method design combining longitudinal analysisof financial statement data from 1998-2004 with experimental simulations of investordecision-making under varying measurement reliability conditions. The findings revealseveral original contributions: first, we demonstrate that Level 3 fair value measurements exhibit a paradoxical effect—while intended to provide more relevant information, they actually increase market volatility during downturns due to heighteneduncertainty and heterogeneous valuation models. Second, we identify a ”reliabilitythreshold” phenomenon where markets tolerate measurement uncertainty up to a specific point before reacting with disproportionate volatility. Third, we document thatthe relationship between measurement reliability and market volatility is non-linearand context-dependent, varying significantly across industry sectors and market conditions. These insights challenge conventional assumptions about fair value accounting’suniform effects and provide a more nuanced understanding of how measurement qualityinteracts with market stability. The research contributes to both accounting theory andfinancial market regulation by offering evidence-based recommendations for improvingmeasurement standards and disclosure requirements to mitigate unintended volatilityconsequences while preserving the decision-usefulness of fair value information.